Vascular clues in joint degeneration: a cross-sectional study on the association between aortic knob width, aortic arch calcification, and the severity of hand and knee osteoarthritis - Yakup Erden; Mustafa Sağlam; Mustafa Hüseyin Temel (BMC Musculoskeletal Disorders)
Abstract Background Osteoarthritis (OA) and atherosclerosis (AS) are both chronic, complex conditions that share common risk factors and underlying pathophysiological mechanisms. There is also evidence suggesting that AS contributes to the initiation or progression of OA. In this context, the association between the severity of hand and knee OA and AS was analyzed. Materials and methods A total of 218 patients (174 females and 44 males) aged ≥ 40 years were included in the study. The assessment involved measuring aortic knob width (AKW) and grading aortic arch calcification (AAC) on chest X-rays to determine the severity of AS. The Kellgren-Lawrence (K/L) scoring system was employed to evaluate the severity of knee and hand OA. Hand OA severity was determined by calculating the total K/L scores for 15 joints across both hands, while knee OA severity was assessed by summing the K/L scores of both knees. Results A significant positive relationship was identified between AKW and both hand and knee OA, as well as between AAC and hand OA. Multivariate regression analysis demonstrated that increased AKW was independently associated with greater radiographic severity of both hand and knee OA (p =.041 and p =.002, respectively). AAC was not significantly associated with OA severity in either joint. Conclusion This study highlights a novel relationship between vascular markers, specifically AKW, and OA severity, suggesting possible shared risk factors or mechanisms between cardiovascular and musculoskeletal diseases. While AKW may reflect an association with OA severity and underlying AS, further longitudinal studies are necessary to explore causality and confirm these findings.